Analisis Perbandingan Kinerja Keuangan pada Bank Umum Syariah BUMN (Bank BRI Syariah, Bank Syariah Mandiri dan Bank BNI Syariah) - Deny Ismanto; Dwi Keri Agung Laksono (Jurnal Pasar Modal dan Bisnis, 2020)
This study aims to investigate and prove empirically about the differences between the financial performance of Bank BRI Syariah, Bank Syariah Mandiri and Bank BNI Syariah during the period 2014-2018. This research is a descriptive comparison. The data used is secondary data in the form of financial statements of companies that obtained from published financial statements of Bank Indonesia through www.bi.go.id sites as well as on the official website of each of the banks. Data analysis was performed by using financial ratio analysis of CAR, ROA, ROA, FDR, and the NPF. And analysis techniques were used to compare the performance of Bank BRI Syariah, Bank Syariah Mandiri and Bank BNI Syariah is a method of Anova. Analysis showed that there were significant differences for ROA, ROA and FDR while in the CAR and the NPF is not a significant difference. Bank BRI Syariah financial performance is better in terms of capital of the CAR, ROA and efficiency ratio of the NPF ratio, the performance of Bank Syariah Mandiri in this study was less good than the other two bank, Bank BRI Syariah and Bank BNI Syariah.